Fidelity optimized multiparty quantum teleportation protocol with quantum Shor codes and OSPF method in imperfect local operations. (1st December 2022) - Li, J. X.; Wang, Z. M.; Shi, S. S.; Li, Y. N.; Shang, R. M.; Gu, Y. J.
Abstract: Relying on the probabilistic nature and entanglement property of quantum state, quantum communication will support the theoretically unconditional security and computational efficiency beyond that of classical communication. In this article, we present a fidelity optimized quantum teleportation protocol for multiparty quantum network communication. Firstly, a special transmission mechanism ensures the secure establishment of the channel between the communicators. Secondly, the quantum information is encoded by Shor codes to resist channel noise. Thirdly, the Open Shortest Path First (OSPF) method is of help for establishing the channel between non-adjacent communicators. In this protocol, the special transmission mechanism guarantees the security of quantum communication. The Shor codes improve the fidelity of quantum information. The OSPF method ensures efficient transmission. The effectiveness of the protocol is verified by experiments. Experimental results show that this protocol provides effective qubit fidelity improvements within the range of noise thresholds of . Compared with existing quantum communication protocols, this protocol has better reliability and fidelity performance.